Deadliest Earthquakes (Films Media Group, 2011)
NOVA follows a team of U.S. geologists as they first enter Haiti in the immediate aftermath of the 2010 epic earthquake, hunting for crucial evidence that will help them determine what the risks are of a new killer quake. Could this work one day lead to a breakthrough in predicting quakes before they happen? NOVA investigates intriguing new leads in its gripping investigation of a deadly scientific conundrum.